The increment of planters' income through knowledge transfer of the lemon grass production planning programme - Hassan, Salim; Shamsuddin, Zulkifli; Salim, Norshafiqa; Rosman, Sidek; Suhaimi, Hassan Basri (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
The purpose of this programme is to increase planters’ income through the knowledge transfer on the planning programme of lemon grass production for processing by the industry. A total of three areas of knowledge regarding the lemon grass planting planning programme have been and will be transferred by the UPM lecturers. The knowledge areas are lemon grass production planning programme, the execution of lemon grass planting, and also monitoring the planting and care of lemon grass. Four groups are involved in the programme, namely the industry (Malaysian Biospice Sdn. Bhd.); Graduate Intern (Hassan Basri); planters of lemon grass project (5 people), as well as lecturers (3 persons: 2 UPM, 1 Nilai Polytechnic). The "win-win" approach was used in the implementation of the programme. All parties involved in the programmed received benefits according to their respective enterprise. The industry obtained the raw material supply in accordance with the required schedule, graduate intern experienced managing the lemon grass project for industrial needs, lemon grass planters are able to increase their income through the sales of lemon grass with a predetermined price, and finally lecturers are able to contribute the knowledge needed. The project is implemented for a period of two years and will end on 1st April 2016. Early results showed that a lemon grass production schedule agreed by the graduate intern, the planters and the industry has been prepared by the lecturers involved. At the same time, production activities of lemon grass are performed by the planters and monitored by the graduate intern. There are two major problems during the project implementation, namely the availability of tractors for ploughing land and the shortage of local manpower. However, both problems have been overcome with joint efforts. The second year programme focused on highlighting the self-potential of the graduate intern through the empowerment approach. The programme is expected to help the industry plan the lemon grass production programme, produce an independent project manager and also opens up employment opportunities.